Legal-politicalaspects ofregion development in the context of increase of standard of life of Kazakhstan citizens (Journal of actual problems of jurisprudence, 2018)
Thise article discuss about criteria and corresponding to them indexes of socio-economic development of regions are considered in the conditions of included of Republic of Kazakhstan in the number of the fifty most developed countries of the world. Socio-economic development is based on four main factors: population, natural resources, formation of capital, technique.Key words: region, developed countries, social development, economy growing, intellectual potential.